(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the satisfaction of inpatients at Hanoi Medical University Hospital and identify associated factors in 2024. Subjects and methods: A cross-sectional descriptive study was conducted on 974 inpatients aged over 18 years at Hanoi Medical University Hospital. The study employed a questionnaire developed based on form No.1 guided by Decision No.56/QĐ-BYT issued by the Ministry of Health. Results: The average satisfaction score with medical examination and treatment services at Hanoi Medical University Hospital was 4.71 out of 5, corresponding to a satisfaction rate of 96.5%. Patients aged 40-60 were nearly three times more likely to report high satisfaction compared to those under 40, while those over 60 were 2.17 times more likely to be satisfied than younger patients (p < 0.05). No significant associations were observed between satisfaction levels and gender, place of residence, household living standard, health insurance status, length of hospital stay, or number of treatment episodes. Conclusion: The study results showed an overall mean satisfaction score of 4.71 out of 5.00, with 96.5% of patients classified as “satisfied”. The majority of patients were male, predominantly from rural areas, and the age group 40-60 reported the highest satisfaction levels. These findings highlight the important role of health insurance and service quality at Hanoi Medical University Hospital in meeting patients’ healthcare needs.